Safety and immunogenicity of the malaria candidate vaccines FP9 CS and MVA CS in adult Gambian men. - Imoukhuede, E; Berthoud, T; Milligan, P; Bojang, K; Ismaili, J; Keating, S; Nwakanma, D; Keita, S; Njie, F; Sowe, M; Todryk, S; Laidlaw, S; et al. (2006)
We assessed the safety and immunogenicity of prime-boost vectors encoding the Plasmodium falciparum circumsporozoite (CS) protein expressed either in the attenuated fowl-pox virus (FP9) or modified vaccinia virus Ankara (MVA). Thirty-two adult Gambians in groups of four to eight received one, two or three doses of FP9 CS and/or MVA CS. No serious adverse event was observed following vaccination. The most immunogenic regimen was two doses of FP9 followed by a single dose of MVA 4 weeks later (an average of 1000 IFN-gamma spot forming units/million PBMCs). This level of effector T-cell responses appears higher than that seen in previously reported studies of CS-based candidate malaria vaccines.